2013
DOI: 10.4067/s0717-95022013000200048
|View full text |Cite
|
Sign up to set email alerts
|

Relation of Breast Cancer and Malathion Aerial Spraying in Arica, Chile

Abstract: SUMMARY:Breast cancer mortality has been increasing in Arica Chile where it has surpassed the national rates 11 times between 1990 and 2010. The city of Arica was sprayed with the organophosphrous pesticide malathion in order to control the Mediterranean fly 33 years ago. Moreover we have demonstrated that a malathion treatment induces the formation of breast carcinomas in Sprague Dowley female rats. The objective of this work was to find a relationship between malathion aerial spraying and the increased morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…The other half of them obtained positive associations at statistically significant levels for thyroid cancer 78 , ovarian cancer in menopausal women 78 , prostate cancer 80,88 and its aggressive type 83 , breast cancer 81 , NHL 94,98 and between body mass index and cancer colonization among men who used malathion 89 .…”
Section: Malathionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other half of them obtained positive associations at statistically significant levels for thyroid cancer 78 , ovarian cancer in menopausal women 78 , prostate cancer 80,88 and its aggressive type 83 , breast cancer 81 , NHL 94,98 and between body mass index and cancer colonization among men who used malathion 89 .…”
Section: Malathionmentioning
confidence: 99%
“…In Chile, about 33 years after the first malathion spraying on the city of Arica, Cabello et al 81 conducted a case-control study with women living in the city and women from Iquique, a control city where spraying had never occurred. The authors observed that those with the most extended exposure to malathion were 5.7 times more likely to be diagnosed with breast cancer, besides 30.5% of the cases of metastases found in the exposed group, compared to 16% in the never exposed group (p < 0.05).…”
Section: Malathionmentioning
confidence: 99%
“…En otro estudio, Calaf et al (2009) evaluaron los efectos de pesticidas OP paratión y malatión ante la presencia de E2 en la transformación maligna e inestabilidad genómica e informaron que estos pesticidas, por separado o en combinación con E2 inducen transformación maligna en células mamarias, evidenciado por un incremento significativo en la expresión de las proteínas p53 y c-Ha-ras, cruciales para el proceso del cáncer. Cabello et al (2013) evaluaron la relación entre las 24 aspersiones con malatión realizadas sobre la ciudad de Arica en 1983 y el aumento en la tasa de mortalidad por cáncer de mama observada en dicha ciudad en los últimos años. Los autores encontraron que las mujeres con mayor tiempo de exposición a malatión fueron 5.7 veces más propensas a ser diagnosticadas con cáncer mamario (OR = 5.7, p < 0.02), evidenciándose además metástasis en un 30.5% del grupo expuesto y un 16% del grupo no expuesto.…”
Section: Pág 103unclassified
“…In a Chilean study on the relationship between BC and malathion aerial spraying, Cabello et al extracted additional data on BC patients from medical records 47 . Three studies used databases instead of interviews (Chart 1) 35,36,50 .…”
Section: Methodological Approaches Differed Considerably Among Studiementioning
confidence: 99%